2018
DOI: 10.4149/bll_2018_027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between intracranial pressure and lactate/pyruvate ratio in patients with subarachnoid haemorrhage

Abstract: AIM: The aim of this study was to analyse the relationship between intracranial pressure (intracranial pressure monitoring) and lactate pyruvate ratio (cerebral microdialysis) in patients with ruptured intracranial aneurysms. METHODS: In a group of fi fteen patients, intracranial pressure and lactate/pyruvate ratios were measured and logged in hourly intervals. The relationship between these two variables was subsequently analysed in two ways. 1) Intracranial hypertension (ICP > 20 mmHg) in the presence of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Manipulation of ICP, such as opening the EVD to reduce pressure in patients with high ICP, resulted in a surge of pyruvate [61]. Similarly in other studies, increased ICP (≥ 20 mmHg) on days 1 to 7 after SAH was positively correlated with an elevated ISF LPR (> 25) [62] and decreased cerebral perfusion [50]. The derangement of metabolites occurred prior to the increase in ICP and lowered cerebral perfusion, with over 80% of patients with intracranial hypertension presenting with deranged metabolism (an LPR of greater than 25) prior to the first rise in ICP.…”
Section: Brain Hemodynamics and Lactate And Pyruvatementioning
confidence: 87%
“…Manipulation of ICP, such as opening the EVD to reduce pressure in patients with high ICP, resulted in a surge of pyruvate [61]. Similarly in other studies, increased ICP (≥ 20 mmHg) on days 1 to 7 after SAH was positively correlated with an elevated ISF LPR (> 25) [62] and decreased cerebral perfusion [50]. The derangement of metabolites occurred prior to the increase in ICP and lowered cerebral perfusion, with over 80% of patients with intracranial hypertension presenting with deranged metabolism (an LPR of greater than 25) prior to the first rise in ICP.…”
Section: Brain Hemodynamics and Lactate And Pyruvatementioning
confidence: 87%
“…In recent years, a growing body of clinical evidence has demonstrated that multimodal neural monitoring, including parameters such as ICP, BT, and cerebral oxygen metabolism, plays a crucial role in mitigating the risks of secondary brain injury in individual patients and can serve as valuable predictors for assessing the prognosis after SICH (9,10). Multimodal monitoring is an important reference index for the diagnosis and treatment of clinical neurosurgical diseases, offering valuable insights for the identification and determination of intracranial conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The result found that the lactate/ pyruvate concentration the first 4 days after admission was correlated with Glasgow-Pittsburgh cerebral performance category 30 days after cardiac arrest, whereas the glucose was correlated with the outcomes until 3.5 days after admission 15 . A study suggested that a lactate/ pyruvate higher than 30 was correlated with low cerebral perfusion pressure (CPP), while it was not correlated with increased intra-cranial pressure (ICP) by investigating the data of 1873 cases 16 .…”
Section: Discussionmentioning
confidence: 99%